ENT 600 : OSPREY PACKS, INC. / Annis Syafiqa Anuar - Anuar, Annis Syafiqa (2021)
This case study assignment was commissioned to examine how a company managed to design, manufactures and markets their products. The company that I had chosen to investigate more details on is Osprey, a well-known brand of backpacks. It is certainly recognized as one of the best cardiovascular exercises when it comes to hiking, where it can strengthen muscle control, solid bones and improved coordination. In addition, hiking is not only limited to the benefits of exercise, but also improves a healthy mental outlook and relieves tension. Thus, choosing the best backpack is very crucial to all hikers. One of the backpack that catches my eyes is Osprey Kestrel 48. This is one of the backpack that is produced by Osprey Company, one of the famous backpacks distributor. Even though it holds a lot of advantages, there are also some other disadvantages that need to be modify in order for it to be the best choice of hiking backpack. The first problem rises are the mesh pockets were too small, not great for bottles and easy to tear off. Second, the fabric not completely waterproof, which means it cannot withstand heavy rainfall. Third, the weight of the pack is too heavy, especially for intense climbs or longer hikes. Lastly, lack of safety hazard drawstring such as no reflective materials added for the safety at night. To recap, we need to produce more advanced hiking backpack that include newest technology to resolve the needs of hiker’s enthusiasts.